PARTIAL CHARACTERIZATION AND ANTIMICROBIAL PROPERTY OF SMALL PEPTIDES ISOLATED FROM THE FLOWERS OF MILLINGTONIA HORTENSIS - R, Angayarkanni; G, Sridevi (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The flowers of Millingtonia hortensis were initially screened for the presence of Cu (II) ninhydrin-positive compounds. Purification and characterization of small alpha peptides from the flowers of M. hortensis have been done. Further elucidation of the antimicrobial properties of these small peptides is also taken as part of the work. Methods: Using 80% aqueous ethanol the crude extract was prepared and screening was carried out by a circular paper chromatographic technique. Purification and characterization of small alpha peptides from the flowers of M. hortensis have been done. Further elucidation of the antimicrobial properties of these small peptides by disc diffusion method is also taken as part of the work. Results: Based on the findings of UV–visible spectrophotometer, it is confirmed that the purified compound is a small peptide and might contain glycine, cysteine, and tyrosine or histidine. The result of antimicrobial studies proves the ability of small peptides to function as antimicrobial peptides. Conclusion: It is concluded that the small peptides show an inhibitory effect against various Gram-negative and some Gram-positive bacteria.